Aspects of Named Entity Processing - Levit, Michael (Proc. of ICSLP, 2004)
In this paper we investigate the utility of three aspects of named entity processing: detection, localization and value extraction. We corroborate this task categorization by providing examples of practical applications for each of these subtasks. We also suggest methods for tackling these subtasks, giving particular attention to working with speech data. We employ Support Vector Machines to solve the detection task and show how localization and value extraction can successfully be dealt with using a combination of grammar-based and statistical methods.